Analisis Pemborosan Waktu Pelayanan Dengan Metode Lean Healthcare Dan Failure Mode And Effects Analysis Di RSUD Dr. Soetomo Surabaya - Anthony Surya Wirawan; Dwi Sukma Donoriyanto (Fakultas Teknik Universitas Cenderawasih, 2023)
Dr. Hospital Soetomo Surabaya with minimum service standard data that must be met is customer satisfaction ≥ 90% and waiting time ≤ 60 minutes in accordance with Ministry of Health (Kemenkes) decree no. 129 of 2008. Therefore, the problems faced by the Outpatient Institution Children's Polyclinic include service time Administration takes too long and quality must be improved. The most critical slowness of services at the Children's Polyclinic is in the registration administration section, namely the number of double registrations, disruptions in facilities and nurses who are still lacking in discipline. Applying Lean Healthcare and Failure Mode and Effects Analysis to improve service quality and prevent failures, such as slow service and lack of facilities will help find recommendations for improving these problems, namely reducing double registration of patients by improving data management and registration, repairing and improving maintenance of computer facilities for reducing waiting time due to disturbances and tightening discipline according to SOP.